RECEPTION OF THE ORDER OF WEARING HIJAB IN RIMPU TRADITION: (Study Qs. Al-Ahzab Verse 59) - Shopian Hidayatullah; Ahlan; M. Ridho Rizki Setiawan (UIN Mataram, 2023)
Rimpu is an aurat cloth typical of the mbojo tribe that uses two pieces (dua ndo'o) of cloth called Tembe Nggoli, and has become a hereditary heritage of Siwe Mbojo. In Islam the command to close the aurat is one of the mandatory commands for a Muslim woman balig, as contained in Qs. Al-Ahzab verse 59. This study uses a qualitative approach with descriptive analysis method. By using the theory of Sociology of knowledge Karl Mannheim as a surgical tool in order to trace in depth to the study conducted. So that the data obtained through field observations as well as books, journals and articles related to the discussion. The results of this article indicate that; first, Rimpu in women of the mbojo Tribe Other than as a distinctive tradition that must be maintained, is also part of the submission of the Siwe Mbojo to the teachings of Islam. Second, the Rimpu on the womenof the Mbojo Tribe shows obedience to the commands of Allah and The Messenger of Allah. Third, Rimpu by women of the Mbojo tribe is a symbol of respect, appreciation and selfpreservation efforts of the opposite sex, in line with the purpose of the command to wear the hijab in Qs. Al-Ahzab verse 59.